2021
DOI: 10.1093/alcalc/agab047
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Hospital Escalation-of-Care Referrals for Severe Alcohol-Related Liver Disease with Recent Drinking During the COVID-19 Pandemic

Abstract: Alcohol sales and consumption have increased during the coronavirus disease 2019 pandemic, but their downstream effects on alcohol-related liver disease (ALD) are unclear. We analyzed inter-hospital escalation-of-care referrals to our tertiary care inpatient liver unit across 18 months through December 2020. There was a significant rise in severe ALD with recent unhealthy drinking in our regional community during the pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 14 publications
0
23
0
1
Order By: Relevance
“…The early surge of cirrhosis-related ALD mortality is consistent with prior reports of increased alcohol sales and use during the initial period of the pandemic and increased ALDassociated hospitalization. [10][11][12][13] Recent studies showed that alcohol abuse was independently associated with severe COVID-19 and COVID-19-related death. 14 Another recent study showed an increase in both COVID-19-related and non-COVID-19-related mortality of patients with ALD.…”
Section: Discussionmentioning
confidence: 99%
“…The early surge of cirrhosis-related ALD mortality is consistent with prior reports of increased alcohol sales and use during the initial period of the pandemic and increased ALDassociated hospitalization. [10][11][12][13] Recent studies showed that alcohol abuse was independently associated with severe COVID-19 and COVID-19-related death. 14 Another recent study showed an increase in both COVID-19-related and non-COVID-19-related mortality of patients with ALD.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence indicates that alcohol sales, alcohol consumption, and complications of alcohol use have increased during the pandemic. 1 , 2 , 3 However, there are limited data on nationwide alcohol use disorder (AUD)–related mortality. Here, we use projective modeling to evaluate AUD-related mortality rates in the US from 2012 to 2021, with a focus on trends during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…2 Likewise, another study documented self-reported increases in daily alcohol use. 3 Preliminary reports suggest an increase in hospital admissions for alcohol-related liver disease (ARLD), 4,5 but comparisons with prior years have not yet been documented. We investigated whether new hospital admissions resulting from ARLD increased in the summer of 2020 compared with previous years.…”
mentioning
confidence: 99%